Analysis of the presence of enteroparasites in Lactuca sativa (LETTUCE) sold at fairs and supermarkets in the municipality of Grajaú-Maranhão (Research, Society and Development, 2022)
Among the vegetables, lettuce (Lactuca sativa) stands out as one of the most popular leafy vegetables and consumed fresh. Due to the lack of structural and hygiene conditions, the commercialization of raw products in open markets causes greater exposure to contaminating pathogens. Thus, this study aimed to analyze the presence of enteroparasites in lettuce sold in supermarkets and open markets in the municipality of Grajaú-MA. Samples were collected at two fair stands and four supermarket shelves. The lettuces were separated into leaves, washed manually with distilled water and 5 drops of Tween 80 and left to stand for 3 hours. The resulting liquid was stored in conical cups for sedimentation for 24 hours. The sediment was separated and analyzed under an optical microscope. All investigated samples presented some type of enteroparasites. The results obtained indicated that all samples studied contained some parasitic structure, Entamoeba coli and the nematode eggs, for example, were present in all samples. In addition to protozoa, Ascaris and Trichuris eggs, fungi, yeasts, dirt and other types of single-celled life were found on the observed slides. The most common intestinal parasites were protozoa such as Giárdia lamblia (63.3%) nematode egg (27.3%), and Entamoeba coli. (23.8%). As lettuce (L. sativa) is eaten raw, it is necessary to apply a health education program for farmers to start reducing contamination rates. And for consumers there is a need to wash the leaves correctly before consuming them. Using the recommended hygiene standards, they can avoid ingesting enteroparasites.